Perceived biodiversity of fruit species for urban greenery in Indonesia: Case studies in Bogor, Jakarta, and Yogyakarta (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ruwaida IP, Santosa E, Susila AD, Widodo WD, Wachjar A, Nasrullah N. 2022. Perceived biodiversity of fruit species for urban greenery in Indonesia: Case studies in Bogor, Jakarta, and Yogyakarta. Biodiversitas 23: 3166-3177. Urban greenery planning considering biodiversity scenarios is still rarely studied in Indonesia. This study aims to demonstrate edible fruit species (FS) as the scenario for urban greenery based on interviews with citizens in Indonesian cities. The study was carried out in the cities that have implemented smart city models i.e., Bogor, Jakarta, and Yogyakarta-Indonesia. Interviews were conducted in July-December 2019, involving 420 respondents. The results showed that 77.7% of all respondents agreed with the planting of FS as city greenery. In total for all cities, there were 79 species belonging to 32 families mentioned by the respondents consisting of 41 commercial and 38 underutilized FS. Each respondent was able to mention between 20.4 and 22.8 fruit species, irrespective of city. The ability to mention fruit species was affected by the respondent’s background, especially exposure during childhood to FS, frequency as a domestic tourist, mobility mode, and frequency of visiting city parks. The rationale for selecting FS was the benefit of fruit as a food source, followed by the benefit of ecology, economy, aesthetics, and health. Based on the significant cultural index, mango ranked first as the most preferred commercial fruit species, followed by rambutan, rose apple, orange, papaya, starfruit, guava, avocado, sapodilla, and longan; and for underutilized FS were shoe-button, pinang, nam nam, mulberry, cactus, canistel, cherry, and pear. Value of species richness, Shannon-Wienner, and Simpson diversity indices of FS within a city ranged 0.97 to 1.06, 3.62 to 3.83, and 0.97, respectively. Biodiversity scenarios could be useful information in the greenery planning of smart cities to coop with evolving broader environmental services.